Faktor-Faktor Yang Berhubungan dengan Tingkat Kepatuhan Perawat dalam Melakukan Hand Hygiene: Factors Associated with Nurses' Hand Hygiene Compliance Levels - Tommy Wowor; Andi Mayasari Usman; Mia Atlantic; Niken Rima Fadilla (Journal of Nursing Education and Practice, 2026)
Background: Hand hygiene is a fundamental component of infection prevention and control in healthcare settings. Proper hand hygiene practices play an essential role in reducing the transmission of microorganisms, preventing healthcare-associated infections, and improving patient safety. Nurses are among the healthcare professionals who interact most frequently with patients, making their compliance with hand hygiene procedures crucial in maintaining quality healthcare services. Despite the availability of guidelines and infection prevention programs, compliance with hand hygiene practices remains a challenge in many healthcare facilities. Various individual and environmental factors may influence nurses’ adherence to hand hygiene recommendations.Objective: To analyze the factors associated with nurses’ compliance in performing hand hygiene in the surgical ward.Methodology: This study employed a quantitative design with a cross-sectional approach. The study population consisted of nurses working in the surgical ward, and respondents were selected using a total sampling technique. Data were collected through structured questionnaires that assessed respondents’ characteristics, knowledge, availability of facilities, workload, and hand hygiene compliance. Data analysis was performed using the Chi-square test.Research Results: The findings showed that knowledge, availability of facilities, and workload were significantly associated with nurses’ compliance in performing hand hygiene. Nurses with better knowledge, adequate facilities, and manageable workloads tended to demonstrate higher levels of compliance. In contrast, length of service and gender were not significantly associated with hand hygiene compliance.Conclusion: Nurses’ compliance with hand hygiene is influenced by both individual and organizational factors. Improving knowledge through continuous education, ensuring the availability of adequate facilities, and managing workload effectively are important strategies to enhance hand hygiene compliance. Strengthening these aspects may contribute to better infection prevention practices and improved quality of patient care.